2014
DOI: 10.1097/brs.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pedicle Subtraction and Smith-Petersen Osteotomies in Correcting Thoracic Kyphosis When Closed With a Central Hook-Rod Construct

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…Our experience was a 17.5°in the upper thoracic and 26.2°in the lower thoracic region confirming some limitation due to the rib cage in the upper thoracic spine. The average global thoracic kyphosis reduction in our series was 24.2°which is similar to other series [2][3][4]. The combination of PSO with SPO in the Lewis et al series [3], when possible, showed a better correction of the kyphosis at 36.3°.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our experience was a 17.5°in the upper thoracic and 26.2°in the lower thoracic region confirming some limitation due to the rib cage in the upper thoracic spine. The average global thoracic kyphosis reduction in our series was 24.2°which is similar to other series [2][3][4]. The combination of PSO with SPO in the Lewis et al series [3], when possible, showed a better correction of the kyphosis at 36.3°.…”
Section: Discussionsupporting
confidence: 88%
“…The average global thoracic kyphosis reduction in our series was 24.2°which is similar to other series [2][3][4]. The combination of PSO with SPO in the Lewis et al series [3], when possible, showed a better correction of the kyphosis at 36.3°. Another important point was the risk of anterior vertebral collapse or translation during osteotomy closure.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations